Impaired NK cell recognition of vemurafenib-treated melanoma cells is overcome by simultaneous application of histone deacetylase inhibitors. (1st February 2018) - López-Cobo, Sheila; Pieper, Natalia; Campos-Silva, Carmen; García-Cuesta, Eva M.; Reyburn, Hugh T.; Paschen, Annette; Valés-Gómez, Mar
ABSTRACT: Therapy of metastatic melanoma advanced recently with the clinical implementation of signalling pathway inhibitors, such as vemurafenib, specifically targeting mutant BRAF V600E . In general, patients experience remarkable clinical responses under BRAF inhibitor (BRAFi) treatment but eventually progress within 6–8 months due to resistance development. Responding metastases show an increased immune cell infiltrate, including also NK cells, that, however, is no longer detectable in BRAFi-resistant lesions, suggesting NK cell activity should be exploited to prevent disease progression. Here, we examined the effects of BRAFi on the expression of ligands targeting activating NK cells receptors immediately after treatment onset, prior to resistance development. We demonstrate that BRAF V600E mutant melanoma cells cultured in the presence of vemurafenib, strongly decreased surface expression of ligands for NK activating receptors including the NKG2D-ligand, MICA, and the DNAM-1 ligand, CD155, and became significantly less susceptible to NK cell attack. NKG2D-ligand protein downregulation was due to a significant decrease in mRNA levels, already detectable 24 h after drug treatment. Interestingly, vemurafenib-induced MICA downregulation could be counteracted by treatment of melanoma cells with the histone deacetylase (HDAC) inhibitor (HDACi) sodium butyrate, that also upregulated the DNAM1-ligand, Nectin-2. HDACi treatment enhanced surface expression of NKG2D-ligands in the presence of BRAFi, accompanied by recovery of NK cell recognition, but only upon simultaneous drug application. These results suggest that co-administration of BRAFi and HDAC inhibitors as well as having direct effects on melanoma cell survival, could also synergise to improve NK cell recognition and avoid tumour immune evasion.